1993
DOI: 10.1037/0882-7974.8.3.323
|View full text |Cite
|
Sign up to set email alerts
|

Convoys of social support: An intergenerational analysis.

Abstract: Within the Convoy Model, social networks are viewed as dynamic hierarchic structures surrounding the individual throughout life. As a step toward empirical definition of convoy structure and function across the life span, a bicultural sample (N = 159) of young adult women, their mothers, and their grandmothers were queried. Comparable results were obtained across generations and cultures with regard to network size, the amount of support provided by the network, and the nomination of close family members as pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
2
3

Year Published

1998
1998
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 11 publications
2
47
2
3
Order By: Relevance
“…It has been demonstrated that the network-related selection processes in older age are rather driven by seeking emotional meaning than by seeking emotional support, with emotionally close individuals becoming typical sources of emotional support (Fung and Carstensen 2004). In contrast, networks of younger persons comprise more diverse sources of support, such as work colleagues or acquaintances (e.g., Levitt et al 1993). Thus, selecting a social network mainly consisting of emotionally close social interaction partners may lead to an increased match between receipt of and needs for emotional support by the older individual (Krause 2005).…”
Section: Age Differences Of Social Supportmentioning
confidence: 99%
“…It has been demonstrated that the network-related selection processes in older age are rather driven by seeking emotional meaning than by seeking emotional support, with emotionally close individuals becoming typical sources of emotional support (Fung and Carstensen 2004). In contrast, networks of younger persons comprise more diverse sources of support, such as work colleagues or acquaintances (e.g., Levitt et al 1993). Thus, selecting a social network mainly consisting of emotionally close social interaction partners may lead to an increased match between receipt of and needs for emotional support by the older individual (Krause 2005).…”
Section: Age Differences Of Social Supportmentioning
confidence: 99%
“…Most studies that have explored age differences in support have tended to focus on cross-generational transactions, paying little attention to normative changes that may occur in social support at different developmental stages. There is evidence, however, that such changes do occur, and that variations in the structure and perceived quality of social support is related to these changes (Ishii-Kuntz, 1990;Levitt et al, 1993).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite the numerous studies on gender differences, there have been few studies to date that have examined social support from a life span perspective (Ishii-Kuntz, 1990;Levitt et al, 1993). Most studies that have explored age differences in support have tended to focus on cross-generational transactions, paying little attention to normative changes that may occur in social support at different developmental stages.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This results in older people being more selective in choosing the people with whom they interact socially. Social interaction with people outside of one's family or network of close friends plays a less central role as adults become older (Levitt, Weber, & Guacci, 1993) and older adults tend to use dismissive attachment style more often (Webster, 1997). In this study, this corresponds to older adults reacting to their social goal achievement as if the social goal was less important to them than to younger people.…”
Section: Limitations and Further Studiesmentioning
confidence: 99%